IMPLEMENTASI INTRUSION DETECTION SYSTEM (IDS) MENGGUNAKAN SURICATA PADA LINUX DEBIAN 9 BERBASIS CLOUD VIRTUAL PRIVATE SERVERS (VPS) - Mamay Syani (Politeknik Meta Industri, 2020)
The development of information technology, especially on virtual Private server (VPS) technology in particular that uses Debian Linux operating system, increasingly facilitated with the service Adaya of some VPS providers both locally and non-local, but there is a problem vulnerability if, the server maintainers do not shame testing against the resilience of attacks from outside parties, with the Network Development Life Cycle (NDLC) method is one of the most popular in the Monitoring phase is using Suricata Intrusion Detection System (IDS) software. Suricata is a tool to detect any suspicious activity that could be threatening a network or server with Brute Force technique, DDOS, Port Scanning. Suricata is able to display logs from suspicious activity results in detail with the time, date and IP address of the activity even with the tools used to perform the activity. Also suricata can detect if there is suspicious activity associated with the network..